Pindar, Pelops and Myrtilos Reconsidered - Patay-Horváth, András (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
The main mythological narrative in Pindar’s first Olympian ode was often taken in isolation and the poet’s declaration about his intentions in modifying the traditional tale were also taken at face value. Based on the recent clarification of the famous mythological revision concerning the banquet of Tantalos, this paper offers a new overall interpretation of the poem and concludes that Pindar’s handling of the myth did not derive from some personal desire or moral conviction of the poet but from the necessity to praise his patron appropriately. By ingeniously revising the banquet of Tantalos and by exaggerating a relatively small modification he made, Pindar managed to divert the attention of his audience and concealed another change of fundamental importance, i.e. the elimination of Myrtilos from the chariot race of Pelops and Oinomaos.